Academic library consortia in the Philippines: hanging in the balance. Issue 1 (13th January 2014) - Fresnido, Ana Maria Balenbin; Yap, Joseph Marmol
Abstract : Purpose: – The concept of academic library consortium emerged in the Philippines in the 1970s evidenced by the successive establishment of three consortia namely, the Academic Libraries Book Acquisition Services Association (ALBASA) in 1973, the Inter-Institutional Consortium (IIC) (now South Manila Inter-Institutional Consortium) in 1974, and the Mendiola Consortium (MC) in 1975. This paper aims to find out the experiences and status of selected academic library consortia in the Philippines, namely, the Academic Libraries Book Acquisitions Systems Association, Inc. (ALBASA), the American Corners (also known as American Studies Resource Center (ASRC) in some areas), the Aurora Boulevard Consortium Libraries, Inc. (ABC), the Davao Colleges and University Network (DACUN), the Inter University Consortium (IUC), the Intramuros Library Consortium (ILC), the Mendiola Consortium (MC), the Ortigas Center Library Consortium (OCLC), and the South Manila Inter institutional Consortium (SMI-IC) specifically in terms of the objectives of the different consortia, the activities they undertake and how such relate to the set objectives, the benefits they have enjoyed or continue to enjoy, the issues they have encountered as well as success/failure factors experienced by libraries in joining the different consortia. Design/methodology/approach: – The sample was derived from the review of literature, which also served as basis to come up with the list of existing academic library consortia. The respondents were selected based on the Philippine Association of Academic and Research Librarians (PAARL) directory. Communication was sent via email, telephone, scheduled personal interview and social networking sites (e.g. Facebook). A total of 13 out of 23 (56.52 percent) respondents accomplished the survey questionnaires which were distributed online and manually. Descriptive statistics was used to analyze the results. Findings: – Results of the study revealed that the role academic library consortia play in the development of academic libraries is crucial particularly in the promotion of professional development and resource sharing. As technology greatly influences the way libraries do things, the varying level of technological development among consortium member libraries confirmed to be a major challenge being faced by them today. While majority of the surveyed consortia assessed themselves to be successful, it is evident that there is lack of congruence between the consortia ' s objectives and undertakings. Originality/value: – The paper is a modest contribution to the dearth of literature in Philippine academic library consortia. It also is the first study conducted measuring the success of selected academic consortia and identifying the factors contributing to their success/failure.